2019
DOI: 10.1080/22243534.2019.1653587
|View full text |Cite
|
Sign up to set email alerts
|

What fires up my cooking? The choice for a sustainable cuisine: passion and self-transcendence in the restaurant business

Abstract: The restaurant business is highly unsustainable and the sector contributes to a large extent to environmental pollution. However, some restaurateurs have chosen a more sustainable cuisine. As food sustainability is a contested issue, we have considered several descriptions of food sustainability and have assessed how these are influenced by a passion for hospitality. Theoretically, the choice for sustainable food can be based on a passion for the hospitality business and a passion for sustainability. Surveys w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In response to Jacobs and Klosse's (2016) suggestions, a number of researchers have explored what factors promote or obstruct restaurateurs in developing sustainable menus and practices. While some work links passion for sustainability and organic produce to a restaurateur's likelihood to adopt sustainable cuisine (Enthoven and Brouwer, 2019), restaurant managers are primarily influenced by supplier pressures or customer demand (Raab et al, 2018). Indeed, it has been found that sustainable practices (e.g.…”
Section: Restaurateurs and Sustainabilitymentioning
confidence: 99%
“…In response to Jacobs and Klosse's (2016) suggestions, a number of researchers have explored what factors promote or obstruct restaurateurs in developing sustainable menus and practices. While some work links passion for sustainability and organic produce to a restaurateur's likelihood to adopt sustainable cuisine (Enthoven and Brouwer, 2019), restaurant managers are primarily influenced by supplier pressures or customer demand (Raab et al, 2018). Indeed, it has been found that sustainable practices (e.g.…”
Section: Restaurateurs and Sustainabilitymentioning
confidence: 99%
“…Vegan and vegetarian restaurants (hereafter vegetarian restaurants) can contribute to the creation of sustainable food systems (Enthoven & Brouwer, 2019;Niederle & Schubert, 2020). The spatial distribution of sustainable, i.e.…”
Section: Introductionmentioning
confidence: 99%